Soil autotrophic and heterotrophic respiration in response to different N fertilization and environmental conditions from a cropland in Northeast China. (July 2017) - Chen, Zengming; Xu, Yehong; Fan, Jianling; Yu, Hongyan; Ding, Weixin
Abstract: Partitioning soil respiration (Rs) into its heterotrophic (Rh) and autotrophic (Ra) components is crucial to evaluate the effects of inorganic and organic nitrogen (N) fertilization on carbon (C) cycling in agricultural ecosystems. We carried out a field experiment in a maize cropland in Northeast China using the root exclusion method to separate Rh and Ra, and investigate their responses to different fertilization regimes. These included no N fertilization (CK), inorganic N fertilizer (NPK), 75% urea N plus 25% pig (PM1) or chicken (CM1) manure N, and 50% urea N plus 50% pig (PM2) or chicken (CM2) manure N. Annual Rs was significantly increased from 314 g C m −2 in CK to 389, 366, and 371 g C m −2 in NPK, CM1, and PM2, respectively, and further to 420 g C m −2 in PM1, whereas a similar value to CK was observed in CM2 (327 g C m −2 ). N-induced increases in Rs were largely attributable to the response of Ra (except CM2), which increased by 18–54% due to higher nitrate supply. Rh increased from 183 to 192–209 g C m −2 in plots receiving N fertilizer, with significant increases observed in PM1 and PM2, likely due to the high ammonium and labile organic C concentrations in these treatments. Manure type and application rate had significant effects on Rs and Ra, but not Rh. Compared with CM, PM was more effective in stimulating Ra due to its greater decomposability. Rs and Ra decreased in the order of PM1 > PM2 and CM1 ≥ CM2, presumably because of the lower inorganic N supply with increasing manure application rate. The estimated C sequestration rate shifted from negative in CK and NPK to positive in the manure treatments, especially in PM2 and CM2 that gained 0.44 and 0.49 Mg C ha −1  yr −1, respectively. These results suggested that combined application of half inorganic N plus half organic N might have potential to enhance soil C sequestration in cropland of Northeast China. Highlights: Soil respiration (Rs) was divided into auto- (Ra) and heterotrophic (Rh) component. Ra was more temperature-sensitive than Rh; Rh was more moisture-sensitive than Ra. Increase in Rs by N fertilization was largely due to the response of Ra. Type and application rate of organic fertilizer affected Rs and Ra, but not Rh. Applying half inorganic N plus half organic N potentially enhanced C sequestration.